Synchronization of a New Chaotic System Using Adaptive Control: Design and Experimental Implementation - Alfredo Roldán-Caballero; J. Humberto Pérez-Cruz; Eduardo Hernández-Márquez; José Rafael García-Sánchez; Mario Ponce-Silva; Jose de Jesus Rubio; Miguel Gabriel Villarreal-Cervantes; Jesús Martínez-Martínez; Enrique García-Trinidad; Alejandro Mendoza-Chegue (Complexity, 2023)
This paper presents the design of an adaptive controller that solves the synchronization control problem of two identical Nwachioma chaotic systems in a master-slave configuration. The closed-loop stability is guaranteed by means of a Lyapunov-like analysis. With the aim of verifying the feasibility and performance of the proposed approach, a comparison with an active control algorithm is developed at the numerical simulation level. Based on such results, the master-slave Nwachioma chaotic system in closed-loop with adaptive control is now being experimentally tested by using two personal computers and two low-cost Arduino UNO boards. The experimental results not only show the good performance of the adaptive control but also that Arduino UNO boards are an excellent option for the experimental setup.